National doping prevention guidelines: Intent, efficacy and lessons learned - A 4-year evaluation. Issue 1 (December 2016) - Wippert, Pia-Maria; Fließer, Michael
Abstract Background Doping presents a potential health risk for young athletes. Prevention programs are intended to prevent doping by educating athletes about banned substances. However, such programs have their limitations in practice. This led Germany to introduce the National Doping Prevention Plan (NDPP), in hopes of ameliorating the situation among young elite athletes. Two studies examined 1) the degree to which the NDPP led to improved prevention efforts in elite sport schools, and 2) the extent to which newly developed prevention activities of the national anti-doping agency (NADA) based on the NDPP have improved knowledge among young athletes within elite sports schools. Methods The first objective was investigated in a longitudinal study (Study I: t0 = baseline, t1 = follow-up 4 years after NDPP introduction) withN = 22 teachers engaged in doping prevention in elite sports schools. The second objective was evaluated in a cross-sectional comparison study (Study II) inN = 213 elite sports school students (54.5 % male, 45.5 % female, ageM = 16.7 ± 1.3 years (all students had received the improved NDDP measure in school; one student group had received additionally NADA anti-doping activities and a control group did not). Descriptive statistics were calculated, followed by McNemar tests, Wilcoxon tests and Analysis of Covariance (ANCOVA). Results Results indicate that 4 years after the introduction of the NDPP there have been limited structural changes with regard to the frequency, type, and scope of doping prevention in elite sport schools. On the other hand, in study II, elite sport school students who received further NADA anti-doping activities performed better on an anti-doping knowledge test than students who did not take part (F(1, 207) = 33.99, p <0.001), although this difference was small. Conclusion The integration of doping-prevention in elite sport schools as part of the NDPP was only partially successful. The results of the evaluation indicate that the introduction of the NDPP has contributed more to a change in the content of doping prevention activities than to a structural transformation in anti-doping education in elite sport schools. Moreover, while students who did receive additional education in the form of the NDPP"booster sessions" had significantly more knowledge about doping than students who did not receive such education, this difference was only small and may not translate to actual behavior.